2022
DOI: 10.1149/2162-8777/aca17c
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of 2,6-Pyridinedicarboxylic Acid Modified Porous Polypyrrole Electrodes and Its Energy Storage Application

Abstract: The well-designed porous polypyrrole/dicarboxylic acid (PPy/DCA) (0.02) electrodes were successfully synthesized by hydrothermal method. In this study, the interesting structural properties of the synthesized electrodes were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermal gravimetric analysis (TG-DTA), Brunauer–Emmett–Teller (BET) and scanning electron microscopy (SEM). The scanning electron microscopy results showed that a large number of random pores were for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…[81][82][83] Within this framework, cyclic voltammetry, electrochemical impedance spectroscopy, and galvanostatic charge- discharge techniques were employed to explore the fundamental capacitive properties of the coin cell type asymmetric supercapacitors. [84][85][86] The observed rectangular shapes and currents in the cyclic voltammograms were found to be directly correlated with the capacitive behaviors of the materials. 82 Cyclic voltammetric analyses were performed to examine the electrochemical behavior of asymmetric supercapacitors prepared using Cl-GO, CS, and graphite.…”
Section: Resultsmentioning
confidence: 77%
“…[81][82][83] Within this framework, cyclic voltammetry, electrochemical impedance spectroscopy, and galvanostatic charge- discharge techniques were employed to explore the fundamental capacitive properties of the coin cell type asymmetric supercapacitors. [84][85][86] The observed rectangular shapes and currents in the cyclic voltammograms were found to be directly correlated with the capacitive behaviors of the materials. 82 Cyclic voltammetric analyses were performed to examine the electrochemical behavior of asymmetric supercapacitors prepared using Cl-GO, CS, and graphite.…”
Section: Resultsmentioning
confidence: 77%
“…16,43,74,[78][79][80] The Cdl value, on the other hand, was at the highest level after 1000 cycles, in this case, it showed that the interaction at the electrode/electrolyte interface was the highest and the double layer capacitance is the highest in these cycles. 16,43,74,[81][82][83][84] To determine the charge-discharge behavior of the supercapacitor, galvanostatic charge-discharge tests were performed to PANI/SGO/NGO-3 including supercapacitor at a current density of 0.1 A g −1 between 0 and 1.5 V (Fig. 10d).…”
Section: Resultsmentioning
confidence: 99%
“…Voltammograms were acquired over a potential range of À0.5 V to +0.5 V utilizing a reference electrode composed of Ag/AgCl and a counter electrode composed of Pt wire (99.99%). 51 An increase in the concentration of NaB in doped PEDOT:PSS/GCE electrodes from 0.3 mg ml À1 to 2.5 mg ml À1 was accompanied by a corresponding increase in areas of the voltammograms. While the increase in ZnB doping did not result in a corresponding increase in the CV areas compared to the difference in concentrations, the area values were significantly greater than those of the PEDOT:PSS electrode by itself.…”
Section: Electrochemical Propertiesmentioning
confidence: 97%